2008
DOI: 10.1016/j.lungcan.2007.08.025
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 protein expression predicts the response of cisplatin-based neoadjuvant chemotherapy in non-small-cell lung cancer

Abstract: The excision repair cross-complementation group 1 (ERCC1) and BRCA1 have been identified as predictors of clinical outcomes among patients with non-small-cell lung cancer (NSCLC) treated with cisplatin-based chemotherapy. In this study, we immunohistochemically examined the ERCC1 and BRCA1 protein expression levels in 35 patients with metastatic mediastinal lymph nodes obtained prior to treatment as retrospective study. These patients had been enrolled in our studies on neoadjuvant chemotherapy with cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 28 publications
1
59
1
2
Order By: Relevance
“…As an excision nuclease within the NER pathway, excision repair cross complementing group 1 (ERCC1) has been reported to play a major role in the response to platinum-based chemotherapy. Studies have shown that the higher the ERCC1 expression levels, the less sensitive the tumors to platinum therapies [4][5][6][7] . Recently, a single nucleotide polymorphism at codon 118 (C→T) was reported to be associated with altered ERCC1 mRNA levels [8] and clinical outcome in cancer patients treated with platinum-based chemotherapy [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…As an excision nuclease within the NER pathway, excision repair cross complementing group 1 (ERCC1) has been reported to play a major role in the response to platinum-based chemotherapy. Studies have shown that the higher the ERCC1 expression levels, the less sensitive the tumors to platinum therapies [4][5][6][7] . Recently, a single nucleotide polymorphism at codon 118 (C→T) was reported to be associated with altered ERCC1 mRNA levels [8] and clinical outcome in cancer patients treated with platinum-based chemotherapy [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…, 종양 조 직에서 excision repair cross-complementing 1 (ERCC1) mRNA의 발현이 항암화학요법에 대한 반응을 예측할 수 있음을 보여주는 연구도 있었다 23,24 . Epidermal growth factor receptor (EGFR) gene copy 수와 EGFR mutations 이 epidermal growth factor receptor tyrosine kinase inhibitors에 대한 결과를 예측할 수 있을 것이라는 보고가 있었다 25,26 .…”
Section: 양전자 방출 단층촬영에서 나타난 골수 대사활성도unclassified
“…Studies have shown that ERCC1, as an excision nuclease within the NER pathway, play a crucial role in response to platinum-based chemotherapy (Bramson and Panasci, 1993;Olaussen et al, 2006;Kwon et al, 2007) and overexpression of ERCC1 is correlated with less sensitive of tumor cells to platinum therapies (Kwon et al, 2007;Fujii et al, 2008). C8092A (rs3212986) is a common polymorphism of ERCC1.…”
Section: Introductionmentioning
confidence: 99%